Multidisciplinary teaching atlas of the pancreas : radiological, surgical, and pathological correlations /: radiological, surgical, and pathological correlations. ([2016]) - Casillas, Javier; Levi, Joe U; Quiroz, Alexander O; Ruiz-Cordero, Roberto; Garcia-Buitrago, Monica T; Sleeman, Danny
No abstract available